Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, Rasio Efektivitas dan Rasio Kemandirian Terhadap Indeks Pembangunan Manusia - Siti Munfarida; Eko Priyojadmiko (AMAR (Andalas Management Review), 2020)
The aim of this research to analyze the effect of original local government revenue, Dana Alokasi Umum (DAU), effectivity ratio and independence ratio on the Human Development Index (HDI).Quantitative research methode was used in this reasearch. The population are 35 Kabupaten/Kota at Central Java Province in 2015-2017. With purposive sampling technique was taken as many as 24 of the samples that can be analyzed. The data analysis methode using panel data regression analysis. And the data processed using Eviews 10.The result showed that, first original local government revenue have positive signifficant influence on human development index. Second, dana alokasi umum have p positive signifficant influence on human development index. Independence ratio doesn’t have signifficant effected on human development index. Effectivity ratio doesn’t have signifficant effected on HDI.